ALIH MEDIA BAHAN PUSTAKA DI PERPUSTAKAAN INSTITUT AGAMA ISLAM NEGERI (IAIN) PONTIANAK - Kholifah Leyginawati; Atiqa Nur Latifa Hanum (Universitas Tanjungpura, 2020)
Abstract This research discussed the Transfer of Media, Library collection in the Libraries of Pontianak State Islamic Institute (IAIN) library. The purpose of this research was to see what collections the media will change, and the purpose of this changing the media for library collections. This research uses qualitative methods with descriptive research from. Collecting data in this study by observation, interviews, and documentation. The informants in this study was the head of the library and staff of Library. The results of this study indicate that the library of the Islamic Institute of Pontianak State Islamic Institute (IAIN) library, in the collection of student scientific works, grant books from lecturers, and IAIN educational staff is carried out by transferring media. Total collection of scientific works of students there are 1,398 book titles and the number of grants from IAIN lecturers and academic staff there are 324 titles. Switching media was chosen as an efferot to preserve library collection to avoid damage to library collection and to avoid lack of space in the library. Media transfer was carried out at the IAIN library with process of inventory collection, scanning, editing, file conversion to digital form and media to PDF form.Keywords: digital, media transfer, preservation